The Relationship between Ethical Justice & Practical Wisdom: Aristotle's and Ghazali's Viewpoints - Ghoreyshi, Marieh Seyyed; Nazhat, Ibrahim; Rezaee, Ghodratallah (Ciência e Natura, 2015)
The theory of justice is one of crucial principles of philosophical and rational principles in all Greek philosophical schools and then in Islamic morality and ethics. A large number of morality philosophers and exegetes use different concepts of justice interchangeably. They do not make any distinction between justice as a perfect virtue and justice as a component of virtues because they mix the true mediocrity with mediocrity of actions. Aristotle and Ghazali are of philosophers who concentrated on this crucial mixture. This study initially analyzes Aristotle's and Ghazali's mediocrity. Then, it highlights the practical wisdom status and examines justice as a perfect virtue from these scholars' viewpoints. Finally, ethical justice and practical wisdom identicality is evaluated.